Electrolyte analysis of pleural effusion for discrimination between seawater and freshwater drowning in decomposed bodies - Torimitsu, Suguru; Yajima, Daisuke; Inokuchi, Go; Makino, Yohsuke; Motomura, Ayumi; Chiba, Fumiko; Yamaguchi, Rutsuko; Hoshioka, Yumi; Tsuneya, Shigeki; Iwase, Hirotaro (Journal of Forensic and Legal Medicine, 2022)
The diagnosis of drowning is an important issue in forensic investigations. Moreover, discriminating between seawater and freshwater drowning is crucial to identify where the drowning occurred. The present study aimed to investigate electrolyte concentrations in pleural fluid in decomposed bodies in late postmortem intervals and derive cut-off values for the diagnosis of seawater and freshwater drowning. Data were collected from 44 seawater drowning cases, 60 freshwater drowning cases, and 30 non-drowning cases with pleural effusion which served as controls. The levels of sodium ion (Na+), potassium ion (K+), and chloride ion (Cl−) of pleural fluid were measured, and two indices were calculated: summation of Na+ and K+ levels (SUM Na + K), and summation of Na+, K+, and Cl− levels (SUM Na + K + Cl). The means of the three ion concentrations and two indices significantly differed between the three groups (p < 0.0001). The receiver operating characteristic analysis revealed that the sensitivity and specificity were both 1.000 for SUM Na + K + Cl of 288.3 mEq/L between the seawater and control groups. The Na+ value of 109.0 mEq/L also had a high sensitivity of 0.977 and a specificity of 0.933 in the seawater and control groups. The sensitivity and specificity were 0.967 and 1.000, respectively, for SUM Na + K of 123.2 mEq/L between the freshwater and control groups. The electrolyte concentrations in pleural effusion may be useful for the diagnosis of drowning in decomposed bodies with a longer postmortem interval. [Display omitted] •We investigated electrolyte levels in pleural fluid in decomposed cases.•Sodium ion (Na+), potassium ion (K+), and chloride ion (Cl−) levels were measured.•SUMNa + K and SUMNa + K + Cl were defined as indices of drowning.•SUM Na + K + Cl and Na + values may be useful for the diagnosis of seawater drowning.•SUM Na + K may be useful for the diagnosis of freshwater drowning.